Photostability of amine-free CsPbBr3 perovskite nanocrystals under continuous UV illumination - Bonato, Luiz Gustavo; Guilherme Dal Poggetto; Moral, Raphael Fernando; Brener Rodrigo de Carvalho Vale; Germino, José Carlos; Diogo Burigo Almeida; Santiago, Patrícia; Fernandez, Pablo Sebastian; Tormena, Claudio Francisco; Padilha, Lázaro A; Nogueira, Ana Flávia (Journal of materials chemistry. C, Materials for optical and electronic devices, 2023)
Despite all the recent progress on understanding the optoelectronic and structural properties of the CsPbX3 perovskite nanocrystals (PNCs), the impact of the ligands on their photostability, under continuous UV light soaking, is still ambiguous. To address this subject, in this work, we have investigated the influence of the organic ligand on the photophysics of PNCs by comparing the emission behaviour of CsPbBr3 PNCs capped with oleate (OA) and oleylphosphate (OPA). Based on our experimental observations, we propose two different mechanisms to explain their photostability under continuous UV illumination. We hypothesize that the UV illumination promotes a reconstruction of the nanocrystals’ surface, and this process depends on the equilibrium between desorption and adsorption of the surface ligands. In the case of oleate-capped PNCs, this reconstruction is delayed, and even hampered, due to the steric hindered Pb–oleate that desorbs from the surface. In contrast, for the oleylphosphate-caped PNCs, the detached Pb–oleylphosphate can re-adsorb to the surface soon after it leaves because the steric effects are less critical. The results reported here suggest that alkylphosphate ligands can be used to improve the photostability of colloidal PNCs dispersions, an important step towards applications that require continuous excitation, such as back-illuminated LEDs and solar cells.